Constituent Human Rights - Björö, Morgan ; 0009-0006-8141-1937 (Law and Critique, 2025)
This paper explores and develops the concept of constituent human rights. The paper asks what a constituent element within human rights would look like and how such rights could exist on their own outside of the constituted juridico-political sphere or the human rights regime. To understand this, the paper draws on Antonio Negri’s concept of constituent power in order to draw out its implications for a politics of constituent rights. It furthermore places constituent human rights within the tradition of critical theory and radical politics of human rights. On the one hand, it contrasts constituent human rights with the theories of Jacques Rancière and Judith Butler. On the other hand, it develops the constituent element further in dialogue with the radical human rights tradition. In this way, the paper shows that constituent human rights are the rights brought into being by social movements themselves and that a dynamic and critical approach to rights should acknowledge the way movements produce, generate, and create rights.
Keywords: Constituent power; Antonio Negri; Human rights; Critical Theory; Radical politics